2021
DOI: 10.2196/19074
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patients’ Ability to Review Electronic Health Record Information to Identify Potential Errors: Cross-sectional Web-Based Survey

Abstract: Background Sharing personal health information positively impacts quality of care across several domains, and particularly, safety and patient-centeredness. Patients may identify and flag up inconsistencies in their electronic health records (EHRs), leading to improved information quality and patient safety. However, in order to identify potential errors, patients need to be able to understand the information contained in their EHRs. Objective The aim o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…A growing body of evidence supports providing patients access to their electronic health records to improve several aspects of quality of care, including patient safety [ 1 - 3 ], patient-centeredness [ 4 , 5 ], and effectiveness [ 3 ]. Patient portals are currently recognized as a promising mechanism for improving health care data sharing with patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence supports providing patients access to their electronic health records to improve several aspects of quality of care, including patient safety [ 1 - 3 ], patient-centeredness [ 4 , 5 ], and effectiveness [ 3 ]. Patient portals are currently recognized as a promising mechanism for improving health care data sharing with patients.…”
Section: Introductionmentioning
confidence: 99%
“…If a patient’s primary care practice has signed up, data such as allergies, medications, and diagnoses will also be visible to them. Patients may access their records whenever they wish to review information or when notified about new information, such as available test results [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, prior U.S. and European studies have identified medical terminology as one impediment to patients' understanding of their records. 13 39 40 41 42 43 44 45 Patients with lower education may also be less likely to be engaged in shared medical decision-making with their clinician, 46 which may suggest a lower likelihood of reporting errors. However, in our study, we did not find education level to be a predictor of requesting corrections to medical records.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some U.S. and European studies have reported higher rates of error perception (12–38%) among patients when reading their records. 12 39 44 47 48 The discrepancy between error perception and formally requesting corrections by the health system may be partly explained by patients who may be experiencing challenges with navigating processes for requesting corrections, 11 44 patients who may not perceive the error to be serious enough to warrant formal actions, 44 or patients who may be hesitant on potential adverse effects on their relationships with their clinician or staff. 49 Furthermore, some correction requests may not be clinically or ethically appropriate to complete.…”
Section: Discussionmentioning
confidence: 99%
“…Errors in electronic health records (EHRs) are not uncommon and are known to contribute to patient safety incidents [ 1 ]. Up to 60% of patient records may include inaccuracies or omissions, such as errors in patients’ diagnoses, medical history, medications, allergies, test results, procedures, contact information, and appointment details [ 2 - 6 ]. Early EHR systems largely reflect traditional paper–based records with records containing large amounts of unstructured free text stored in a digital format.…”
Section: Introductionmentioning
confidence: 99%